Neurokinin-1 Receptor Immunoreactive Neuronal Elements in the Superficial Dorsal Horn of the Chicken Spinal Cord: With Special Reference to Their Relationship with the Tachykinin-containing Central Axon Terminals in Synaptic Glomeruli - Sakamoto, Hiroshi (Japan Society of Histochemistry and Cytochemistry, 2009)
Synaptic glomeruli that involve tachykinin-containing primary afferent central terminals are numerous in lamina II of the chicken spinal cord. Therefore, a certain amount of noxious information is likely to be modulated in these structures in chickens. In this study, we used immunohistochemistry with confocal and electron microscopy to investigate whether neurokinin-1 receptor (NK-1R)-expressing neuronal elements are in contact with the central primary afferent terminals in synaptic glomeruli of the chicken spinal cord. We also investigated which neuronal elements (axon terminals, dendrites, cell bodies) and which neurons in the spinal cord possess NK-1R, and are possibly influenced by tachykinin in the glomeruli. By confocal microscopy, NK-1R immunoreactivities were seen in a variety of neuronal cell bodies, their dendrites and smaller fibers of unknown origin. Some of the NK-1R immunoreactive profiles also expressed GABA immunoreactivities. A close association was observed between the NK-1R-immunoreactive neurons and tachykinin-immunoreactive axonal varicosities. By electron microscopy, NK-1R immunoreactivity was seen in cell bodies, conventional dendrites and vesicle-containing dendrites in laminae I and II. Among these elements, dendrites and vesicle-containing dendrites made contact with tachykinin-containing central terminals in the synaptic glomeruli. These results indicate that tachykinin-containing central terminals in the chicken spinal cord can modulate second-order neuronal elements in the synaptic glomeruli.